PORTAL PENJUALAN IKAN BERBASIS WEB DI KABUPATEN KAMPAR (ANALYSIS) Studi Kasus (Kebupaten Kampar) - Wita Huljannah; Deddy Gusman; Novi Yona Sidratul Munti (Jurnal Inovasi Teknik Informatika, 2021)
The Fisheries Service of Kampar Bangkinang Regency, City of targets and realization of fishery production from 2014 to 2020 shows that the realization always exceeds the existing target. Based on these data, we see the number of requests for fish production is very high but in reality the current transaction process is very conventional or uses manual bookkeeping. Fish is one source of food that is often consumed daily, with is delicious taste and high nutritional content of fish being the reason people consumw it. Likewise, the growth of fish sales business activities in Kampar Regenery is quite high, especially in Kampar District. The large market demand is not supported by current marketing, which results in only a few people knowing the products sold by famers. Therefore, the problem in this case is the lack of marketing of products sold by traders. Therefore, a Web-Based Fish Sales Portal will be created in Kampar Regency specifically for Kampar District to develop fish farmer products using the PHP programming language and MYSQL database which is better known as E-Commerce (Electronic Commerce). The advantage in the web-based sales system is that it can make it easier for buyers and breeders to process online purchase transactions which can save time and costs compared to buying directly to the farmer’s location.